2016
DOI: 10.1002/tcr.201600065
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Nonlinear Optical Dendrimers and Dendronized Hyperbranched Polymers

Abstract: Second-order nonlinear optical (NLO) dendrimers with a special topological structure were regarded as the most promising candidates for practical applications in the field of optoelectronic materials. Dendronized hyperbranched polymers (DHPs), a new type of polymers with dendritic structures, proposed and named by us recently, demonstrated interesting properties and some advantages over other polymers. Some of our work concerning these two types of polymers are presented herein, especially focusing on the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 158 publications
0
35
0
Order By: Relevance
“…A review article was published by Li et al to demonstrate the new design strategies for second‐order NLO polymers with a concept of suitable isolation group. Very recently, a comprehensive review on second‐order NLO dendrimers and dendronized hyperbranched polymers was reported in the literature . This review mainly emphasized on the synthetic process with possible tunable topological structures of NLO dendrimers for the enhancement of second‐order coefficients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review article was published by Li et al to demonstrate the new design strategies for second‐order NLO polymers with a concept of suitable isolation group. Very recently, a comprehensive review on second‐order NLO dendrimers and dendronized hyperbranched polymers was reported in the literature . This review mainly emphasized on the synthetic process with possible tunable topological structures of NLO dendrimers for the enhancement of second‐order coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…25 For instance, Rutkis et al 26 hyperbranched polymers was reported in the literature. 28 This review mainly emphasized on the synthetic process with possible tunable topological structures of NLO dendrimers for the enhancement of second-order coefficients.…”
mentioning
confidence: 99%
“…The design and search of novel promising chromophores materials for the optoelectronic applications is very important for modern organic materials science engineering due to their promising parameters with respect to high-speed and broadband telecommunication technology [1][2][3][4][5][6]. For today different materials are just used for the nonlinear optical and electrooptical laser modulators [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[54,55] As the merger of the two families of dendrimers and polymers, dendronized polymers are macromolecules in which perfectly branched dendrons are attached as pendant groups onto a linear polymer backbone affording a structure where many active termini surround a single chain. [56][57][58][59][60][61] Due to their unique tailorable structures and physicochemical properties, [62][63][64][65][66][67][68] dendronized polymers have attracted significant attention in the field of nanoscience and bioscience. [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70] Few reports have focused on the synthesis and application of dendronized metallopolymers; [71,72] however, presumably due to their challenging synthesis.…”
mentioning
confidence: 99%